The relationship between the effectiveness of performing technical elements and indicators of static and dynamic balance in young acrobats 6-7 years old - T. Chernykh; V. Mulyk; K. Mulyk; А. Skaliy; А. Ostrowski; T. Skaliy (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to determine the relationship between the performance of basic elements and indicators of static and dynamic balance in the training process of young acrobats 6-7 years. Material and methods. The study involved 16 young acrobats at the stage of initial training (age 6-7 years). All parents of the participants gave written consent for the participation of children in the study. The study involved testing the technique of performing basic elements of sports acrobatics and assessing the static and dynamic balance of young athletes. The relationship between (swallow, shoulder blade, forward squat, wheel (sideways overturning), bridges) and static and dynamic equilibrium tests was determined. Spearman's rank correlation coefficient method was used as a method of statistical analysis. Results. It is established that the largest relationship between the performance of basic elements and static balance in the basic exercises of young acrobats have: Romberg's test with the elements "Swallow", "Stand on the shoulders", "Bridge"; Biryuk test with elements "Swallow", "Wheel", "Bridge"; balance "Swallow" with elements "Swallow", "Wheel"; static equilibrium test with the elements "Swallow", "Rack on the shoulders", "Rolling forward with a squat", "Wheel". Reliable values ​​of the correlation coefficient were established between the tests of dynamic balance and the basic elements of sports acrobatics in young athletes 6-7 years, namely: "Swallow", "Flip forward with a squat", "Wheel" and "Bridge". The analysis of special tests of static and dynamic balance in mastering the basic elements of acrobatics at the first stage of long-term training makes it possible to use them to determine the level of coordination capabilities of young athletes and further improve the use of acrobatic exercises. Conclusions. A reliable relationship between the performance of basic exercises and indicators of static and dynamic balance in young acrobats at the initial stage of training. It is shown that the level of static and dynamic balance is of great importance for the assimilation and improvement of basic elements of technology by young acrobats 6-7 years. Static and dynamic balance tests can be used to individually build training programs and young acrobats. It is shown that sports acrobatics is a significant means of developing the balance of children 6-7 years.